EIA in the transboundary context of the Arctic Ocean A critical approach on marine petroleum development - Salacha, Andromachi (UiT Norges arktiske universitet, 2021)
Gradual depletion of worldwide petroleum deposits has made the pristine and rich in oil and gas Arctic Marine Region particularly attractive. Petroleum companies have been launching extensive exploration into seabed resources. The Thesis expounds the extent of the duty of States to conduct a transboundary environmental impact assessment (TEIA) prior to offshore hydrocarbon activity in the Arctic Ocean as part of the customary law principle of no harm with particular emphasis on the relevant provisions of the Espoo Convention. The paper outlines the Convention on Environmental Impact Assessment in a Transboundary Context (Espoo Convention) and its application in the Arctic marine region, examining its effectiveness and weaknesses in the comparative light of alternative frameworks, such as the guidelines of the Arctic Council, the Convention on the Law of the Sea, and the Nordic Environmental Protection Convention. Finally, the author make a preliminary analysis of the consequences of a TEIA procedure.